Structural Properties, Cytotoxicity, and Anti-Inflammatory Activity of Silver(I) Complexes with tris(p-tolyl)Phosphine and 5-Chloro-2-Mercaptobenzothiazole - L. Kyros; N. Kourkoumelis; M. Kubicki; L. Male; M. B. Hursthouse; I. I. Verginadis; E. Gouma; S. Karkabounas; K. Charalabopoulos; S. K. Hadjikakou (Bioinorganic Chemistry and Applications)
The synthesis and characterization of the silver(I) chloride complex of formula {[AgCI(CMBZT)(TPTP)2]⋅(MeOH)} (1) (CMBZT = 5-chloro-2-mercaptobenzothiazole, TPTP = tris(p-tolyl)phosphine) is described. Also the structure of the hydrate derivative {[AgCI(TPTP)3]⋅(0.5⋅H2O)} (2) of the corresponding known anhydrous silver complex (Zartilas et al., 2009), and the polymorph 3 of the known [AgI(TPTP)3] complex (Zartilas et al., 2009) were determined and compared with the known ones. In addition, the structure of the known one silver(I) cluster {[AgI(TPTP)]4} (4) (Meijboom et al., 2009) was re-determined at 120(2) K and possible Ag-Ag interactions were analyzed. The compounds 1–4 were characterized by X-ray crystallography at r.t (1) and 120 K (2–4). All these complexes and {[(Et3NH)+]2⋅[Ag6(μ3-Hmna)4(μ3-mna)2]2−⋅(DMSO)2⋅(H2O)} (5) (Hmna = 2-mercaptonicotinic acid) were evaluated for cytotoxic and anti-inflammatory activity. The in vitro testing of cytotoxic activity of 1–5 against leiomyosarcoma cancer cells (LMS), were evaluated with Trypan Blue and Thiazolyl Blue Tetrazolium Bromide or 3-(4.5-dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide (MTT) assays. The flow cytometry assay for complex 1 and showed that at 15 μM of 1, 62.38% of LMS cells undergo apoptosis, while 7% of LMS cells undergo cell necrosis. The antitumor activity of 3 is comparable with that of its reported polymorph (Zartilas et al., 2009). The anti-inflammatory, activity of complexes 1–3 and 5 was also studied. The activity towards cell viability was 2>3>5>1>4, while the order of the inhibitory activity in cell growth proliferation follows the order, 2>3>1>4>5. The anti-inflammatory activity on the other hand is 1>2>5>⋯>3.